Effects of marital psycho-spiritual intervention on personality, communication and attachment among muslim spouses in Kedah, Malaysia - Ahmad, Rosliza (2015)
Statistics released by Jabatan Kemajuan Islam Malaysia (JAKIM) shows that the marital conflict and divorce rates among Muslim increases every year. There are a range of factors associated with marital conflict and divorce. In present study, personality, communication, and attachment are highlighted as the factors that contribute to marital conflict and divorce among Muslim spouses. It is because previous studies have documented that personality has an impact on spousal interaction, marital functioning, and marital adjustment while communication was identified by JAKIM as one of the factors for marital conflict and divorce among Muslim spouses. Besides, studies have shown that Muslim reported higher levels of attachment (especially in anxiety dimension) than Chinese and Indian which were associated with lower marital quality. In an effort to help spouses manage and overcome marital conflicts, Muslim spouses need for an Islamic base according to the religious perspective. A psychoeducational group is a systematic effort to help improve the functioning of Muslim spouses through education and preventative means which widely used in guidance and counseling services. It is a group approach conducted by marriage counselors to educate and disseminating knowledge and skills related to marriage relationships. For that purposes, this study proposed a psychoeducational group known as Marital Psycho-Spiritual Intervention (MP-SI) that focuses on teaching marriage knowledge and skills according to Islamic way. The overarching goal of the present study is to examine the effects of the MP-SI on personality, communication and attachment among Muslim spouses in Kedah, Malaysia. The research design utilized in this study was randomized controlled trials (randomized, pretest, posttest, follow up tests, control group design). This study involved 76 participants. These participants were randomly assigned to either the experimental group (n = 38) or the control group (n = 38). Only participants in the experimental group received treatment of the MP-SI for 6 weeks (2 hours per week). A self-administered questionnaire containing the Ummatic Personality Inventory (UPI), Marital Communication Inventory (MCI), and Revised Adult Attachment Scale (RAAS) were used for collecting data. Data were collected from participants at the baseline assessment prior to the intervention (pretest), then 2 weeks following the completion of the intervention (posttest), and follow up after 2 months (follow up test). Data were analyzed using statistical test, multivariate analysis of variance (MANOVA) and mixed between-within subjects ANOVA. The results from mixed between-within subjects ANOVA showed that there were a statistically significant main effect of time and group for personality, communication, and attachment (avoidance dimension). The result of MANOVA revealed that there was a significant difference between the experimental group and the control group for the dimension of personality; worship, trust, and knowledge. These results reveal valuable information that an Islamic psycho-spiritual approach that emphasizes the spiritual practices and element of nafs (soul), aql (intellect), qalb (heart), and ruh (spirit) help improve Muslim spouses‘ personality, communication and avoidance attachment. In conclusion, the findings of this study give positive reactions on the impact of the Islamic psycho-spiritual approach on human growth. Besides, it leads to theoretical implication for guidance and counseling and a wide range of implication for practice especially for Muslim spouses, marriage counselors, religious departments, and to the public. It is recommended a psychoeducational group of the MP-SI to be used as an intervention in helping Muslim spouses.